The impact of tourism on the sustainability of Gili Trawangan as a natural tourist destination - Adrienta Nayasha Shalsabilla; Mirna Irawan; Muthia A Rafa (Borneo Novelty Publishing, 2024)
Purpose – This article analyzes the impact of tourism on Gili Trawangan's sustainability, focusing on natural resources and the local community.Methodology/Design/Approach – The research uses library research and Focus Group Discussions (FGD) to collect data from relevant articles and journals.Findings – Tourism enhances Gili Trawangan's natural resources, such as beaches and coral reefs, providing economic benefits and job opportunities in sectors like accommodation and transportation. Infrastructure improvements have also been made. However, over-tourism puts pressure on resources and the environment.Originality/Value – This study offers a balanced view of tourism’s impact and stresses the need for careful management to ensure sustainable development while benefiting the local economy.